Serum biochemistry panel of free-living red-handed howler monkeys (Alouatta belzebul) in the Eastern Amazon - Guimarães, Victor Yunes [UNESP]; Justo, André Augusto; Santos, Bruna dos; Ramos, Marcos Montanha [UNESP]; Takahira, Regina Kiomi [UNESP] (Wiley, 2022)
Background: The red-handed howler monkey (Alouatta belzebul) is one of 116 imperiled Brazilian primate species. We aimed to determine the serum biochemical profile of free-ranging red-handed howler monkeys in a highly disturbed area of the eastern Amazon. Methods: We obtained serum samples from 26 monkeys, in which we analyzed 20 biochemical variables. Results and Conclusions: Calcium concentration was significantly lower in adult males (1.82 ± 0.25 mmol/L) than in adult females (2.10 ± 0.50 mmol/L). Both adults (males = 89 ± 85 UI/L, females = 62 ± 23 UI/L) had lower alkaline phosphatase serum activity than juvenile females (178 ± 120 UI/L). Adult male had higher levels of the direct bilirubin (13.9 ± 8.2 µmol/L) and creatinine (74.3 ± 19.4 µmol/L) than juvenile females (5.1 ± 1.4 µmol/L and 38.9 ± 15.0 µmol/L, respectively). This detailed biochemical profile may be useful for the management of red-handed howler monkeys in the wild and to support further studies at ex situ facilities.